How Salafism Forms Millennials’ Religious Understanding: A Case Study from an Indonesian University - Andi Aderus; Ilham Iskandar; Muhammad Irfan Hasanuddin; Firman Firman; Arif Sukino (Ulumuna, 2023)
This research explores the development and influence of the Islamic revivalism movement at Hasanuddin University, South Sulawesi. Employing an in-depth case study, this study focuses on three student groups: Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI), Gema Pembebasan (GEMAPEM), and the Salafi group within the Campus Da'wah Institute. The research found that these groups act as learning communities and active agents in shaping students' religious understanding and practices. The research also shows that these groups' persuasive and systematic methods are important in spreading their teachings and influence. While this research opens up a new understanding of this phenomenon, several limitations were identified, including the scope of the study being limited to one university and the lack of research on other factors that may be influential. This research contributes to a deeper understanding of the dynamics of the Islamic student movement and its influence on university students in Indonesia.